Towards an EHR architecture for mobile citizens - Pedrosa, Tiago (2010)
Electronic Health Records are typically created and stored in different places, by different healthcare providers, using different formats and technology. This poses an obstacle to patient mobility and contributes to scatter personal health related information. Patients constantly move between healthcare providers, searching for a better service, lower prices or specialists. It is important that healthcare professionals, regardless of technology and location, have access to the complete patient health record. The access to this personal health record can be granted through a network (web-based, for example) or can be carried by the patient, in a usb drive, for example. Either approach has to enforce the patient consent to access his information, cope with different types of EHR systems and formats. This paper is an ongoing research, part of a PhD on Electronic Health Records for Mobile Citizens.